Polylysine Enriched Matrices: A Promising Approach for Vascular Grafts - Fusaro, Luca; Calvo Catoira, Marta; Ramella, Martina; Sacco Botto, Federico; Talmon, Maria; Fresu, Luigia Grazia; Hidalgo-Bastida, Araida; Boccafoschi, Francesca (Frontiers in Bioengineering and Biotechnology, 2020)
Cardiovascular diseases represent the leading cause of death in developed countries. Modern surgical methods show poor efficiency in the substitution of small-diameter arteries (<6 mm). Due to the difference in mechanical properties between the native artery and the substitute, the behavior of the vessel wall is a major cause of inefficient substitutions. The use of decellularized scaffolds has shown optimal prospects in different applications for regenerative medicine. The purpose of this work was to obtain polylysine-enriched vascular substitutes, derived from decellularized porcine femoral and carotid arteries. Polylysine acts as a matrix cross-linker, increasing the mechanical resistance of the scaffold with respect to decellularized vessels, without altering the native biocompatibility and hemocompatibility properties. The biological characterization showed an excellent biocompatibility, while mechanical tests displayed that the Young’s modulus of the polylysine-enriched matrix was comparable to native vessel. Burst pressure test demonstrated strengthening of the polylysine-enriched matrix, which can resist to higher pressures with respect to native vessel. Mechanical analyses also show that polylysine-enriched vessels presented minimal degradation compared to native. Concerning hemocompatibility, the performed analyses show that polylysine-enriched matrices increase coagulation time, with respect to commercial Dacron vascular substitutes. Based on these findings, polylysine-enriched decellularized vessels resulted in a promising approach for vascular substitution.